Positive Aging and Precarity Theory, Policy, and Social Reality within a Comparative German Context - Crăciun, Irina Catrinel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores positive aging through the lens of precarity, aiming to ground positive aging theories in current social contexts. In recent years, research on aging has been branded by growing disagreements between supporters of the successful aging model and critical gerontologists who highlight the widening inequalities, disadvantages and precarity that characterize old age. This book comes to fill a gap in knowledge by offering an alternative view on positive aging, informed by precarity and its impact on projections concerning aging. The first part of the book places aging in broader theoretical and empirical context, exploring the complex links between views on aging, successful aging theories, policy and social reality. The second part uses results from a qualitative research conducted in Germany to illustrate the dissonance between successful aging ideals and both negative and positive views on aging as well as aging preparation strategies inspired by precarity. Findings from this section provide a solid starting point for comparisons with countries that are both similar and different from Germany in terms of welfare regimes and aging policies. The final part of the book discusses the psychological implications of these findings within and beyond the German case study and outlines potential solutions for practice. This book provides health psychologists, gerontologists, sociologists, social workers, health professionals as well as students and aging individuals themselves with better understanding of the meaning of aging in precarious times and builds confidence about aging well despite precarity.
Introduction -- Chapter 1: Positive Aging Theories and Views on Aging -- Chapter 2: The Politics of Positive Aging -- Chapter 3: The Social Reality of Aging -- Chapter 4: Perceptions of the Precarious Life: The Middle-Aged Precariat in Germany -- Chapter 5: Views on Aging in Precarious and Financially Secure Individuals -- Chapter 6: Preparing for Old Age -- Chapter 7: Precarity and Views on Aging -- Chapter 8: Precarity and Preparing for Old Age -- Chapter 9: Positive Aging in the Context of Precarity: Conclusions and Implications.
Keywords: Sociology; Social groups; Clinical health psychology; Aging; Geriatrics; Demography; Population; Sociology of Family, Youth and Aging; Health Psychology; Ageing; Geriatrics; Population and Demography